Using a regulator for a servomotor model designed for a prosthetic joint - Álvarez Picaza, Carlos (2014)
Through the modern control theory it is possible to face any problem situation using state equations without considering mathematical rules used from recursive algorithms. The simplification of the various developments will be reflected with new findings, giving values to new concepts such as controllability and stability. This paper seeks to find new work items of the servomotor system by using a regulator, allowing a more controllable and stable performance. The servomotor presented here is designed to generate joint movements of a robotic arm designed for movement rehabilitation of a patient.